Evaluation of the Crossbreeding Scheme and Farmers’ Perception of Awassi and Dorper Crossbred Sheep - Zeleke Tesema; Alemu Kefale; Belay Deribe; Getasew Esayas; Demlie Chanie; Getachew Worku Alebachew; Solomon Tiruneh; Mekonen Shibeshi (Advances in Agriculture)
The objectives of this study were to characterize the performance of crossbred sheep and crossbreeding scheme and to solicit farmers’ opinions about crossbred sheep. A total of 238 respondents were selected from five districts and data were collected through a personal interview, focus group discussion, measurement of animals, and field observation. Continuous type of data were analyzed using different procedures of SAS, while the estimated breeding value (EBV) for distributed rams was estimated by the WOMBAT software fitting animal model. The findings showed that sheep were the most significant species and that they were primarily raised for meat consumption and income generation. The proportions of crossbred sheep were 79.6% in Angot, 61.3% in Dessie zuria, 64.2% in Gazo, 80.6% in Legambo, and 27.5% in the Kobo area. The sheep crossbreeding program was constrained by feed shortage, lack of improved genotype, and diseases. The ongoing sheep crossbreeding program lacks a proper recording scheme, rams were not selected based on genetic merit, not exchanged in time, lack periodic importation of genetically unrelated rams, and lacks fixing the maximum exotic gene level suitable for the production system. The EBVs of Dorper crossbred rams for birth weight and weaning weight were 0.007 kg and 0.273 kg, respectively. Tikur sheep had an earlier age at first lambing (AFL) than Awassi x Tikur sheep. Likewise, the indigenous Wollo sheep had earlier AFL, short lambing interval, and produced a large number of lambs per lifetime than their Awassi crossbreds. Dorper crossbreds were preferred (9.30 - 72.2 times greater and P<0.001) for their growth rate, physical appearance, preference in the market or price, and milk production of ewes compared with indigenous Tumele sheep. The Awassi crossbred sheep were preferred (odds ratio = 12.7– 90.0 and P<0.001) due to their good physical appearance, fast growth rate, wool yield, milk yield, and better preference in the market compared with Tikur and Wollo sheep breeds. The implementation of the crossbreeding program needs some sort of revision, monitoring, and periodic evaluation. Besides, it must be accompanied by improved management to exploit the expected benefits from the crossbreeding program in the low-input production system.